Estudo da corrosão dos aços 1020, inoxidáveis 304L e dúplex SAF 2205 em planta de evaporação do licor de cozimento do processo kraft em indústria de celulose e papel - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The Kraft pulping process responsible for producing more than 130 million tons / year of all pulp produced in the world, is widely spread due to recycling of the chemicals used in pulping, NaOH and Na2S and co-generation of energy and steam for the chemical recovery process, where the residual weak black liquor from the wood cooking, is transformed into heavy black liquor by water evaporation and concentration of the liquor. Evaluating the chemical composition and the difference in solids caused by the water evaporation liquor has been proposed to study the corrosion process caused by the presence of black liquor in different types of metals used in evaporation plant, evaluating the physico-chemical properties of the black liquor in two distinct points of the evaporation plant, the impact caused by the effect of the presence of black liquor in 1020 alloy steel, stainless steel 304L and SAF 2205 duplex and compare the corrosion rate and polarization resistance experienced by the 1020 steel, stainless steel 304L and SAF 2205 duplex at two different concentrations. For verification of corrosion rate, electrochemical concepts were used according to the method ASTM G59-97, where electrodes were fabricated with three types of steels to be studied, the latter being immersed in the solution of black liquor, and evaluated their respective corrosion rates. In all conditions studied the 1020 alloy steel showed the worst corrosion rate and polarization resistance among the studied metals. For the 304L stainless steel and SAF 2205 duplex stainless steel both have acceptable corrosion rates for use with small additions between certain situations between 304L and SAF 2205 duplex steels, but as corrosion rates remained near the various situations studied so it is necessary to evaluate the financial viability of the application of one of the two leagues in the process.
Estudo da corrosão dos aços 1020, inoxidáveis 304L e dúplex SAF 2205 em planta de evaporação do licor de cozimento do processo kraft em indústria de celulose e papel
Keywords: corrosão; aços; licor negro; recuperação química e evaporador; corrosion; steels; Black liquor; chemical recovery and evaporator; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA